SUSTAINABILITY OF BANDUNG CITY SMES THROUGH STRATEGIC MANAGEMENT ACCOUNTING - Jumri Jumri; Samuel Samuel; Depita Anggraini (SEAN Institute, 2022)
This study aims to analyze the strategic management accounting model for MSME sustainability. This research is a type of quantitative research. This study analyzes the factors that influence strategic management accounting for MSME sustainability. The population in this study was Bandung City SMEs with a sample of 98 people. Data collection techniques are observation, interviews, documentation. While the data analysis technique is using SMARTPLS. The results of the study show that the owner's characteristics have a significant and significant effect on the strategic management accounting of MSMEs in Bandung city, while market orientation, business size and accountant participation in strategy formulation have an effect on and not significantly on the strategic management accounting of MSMEs in Bandung city.